Spatio-temporal variation of fish assemblages in Babai River of Dang district, Province No. 5, Nepal - G.C, Punam; Limbu, Jash Hang (Our Nature, 2019)
Spatial and temporal variation of fish assemblages were investigated seasonally from October 2018 to May 2019. Fish assemblages were agglomerated with environmental variables both to spatial and temporal scales. Water temperature, dissolved Oygen, free carbon-dioxide, pH and water velocity of water of each site were measured. Based on analysis of similarities (ANOSIM), fish assemblages were significantly different in spatial variation but not in temporal variation. A total of 1,024 individuals belonging to 5 orders, 9 families and 15 genera and 24 species were collected. The dominated species were Puntius sophore, followed by P. terio, P. ticto and Barilius bendelisis. The Redundancy Analysis (RDA) vindicated that environmental variables of water temperature, pH, water velocity and free carbon-dioxide were found to be contributed variables to shape the fish assemblage structure of Babai River. The cluster analysis delineated that similarity between fish species decreases as the distance of sites increased.